Vanishing Morrey integrability for Riesz potentials in Morrey-Orlicz spaces - Mizuta, Yoshihiro; Shimomura, Tetsu (MATHEMATICA SCANDINAVICA, 2023)
Our aim in this paper is to establish vanishing Morrey integrability for Riesz potentials of functions in Morrey-Orlicz spaces. We discuss the size of the exceptional sets by using a capacity and Hausdorff measure. We also give Trudinger-type exponential Morrey integrability for Riesz potentials of functions in Morrey-Orlicz spaces.